Determination and Comparison of Melissopalynological and Some Chemical Characters of Raw and Processed Honeys - Mayda, Nazlı; Özkök, Aslı (Progress in Nutrition, 2021)
Honey produced by honeybees is presented to the consumer thanks to its high nutritional values. Honey obtained without any filtration or thermal process is called raw honey. However, it is offered to the consumer through various processes for reasons such as preventing crystallization, inhibition microbial growth and extending shelf life. While the during the filtration process honeys lose some of their pollen content and heat treatment applications can affect the chemical and nutritional values of honey. These processes affect the natural structure of honey. In this study, we aimed to analyze and compare of the botanical and chemical structures of raw and processed honeys. Therefore, the melissopalynological, sugar, moisture, invertase, diastase, proline and HMF contents of 20 raw honey (RH) supplied from the beekepers and 20 processed honey (PH) collected from the shelves were investigated and evaluated statistically. As a result, it has been observed that there are significant differences between the total pollen count, moisture %, F/G, HMF, diastase, invertase and proline values of raw honey and processed honey.